Shaolin Physical Conditioning: What’s Old is New Again (Revista de Artes Marciales Asiáticas, 2012)
In recent years, there has been a resurgence of functional fitness training that was practiced in the ancient Shaolin Temple as part of their regular physical conditioning regimen. This type of training—done with equipment (iron rings, bamboo, vases, etc.) or without equipment—can bring a combat-ready fitness level equal to the Shaolin monks. This article introduces iron ring and hard qigong exercises that are based on fundamental principles also found in modern training methods, such as weightlifting, and my own experience and studies in the Shaolin martial tradition. These exercises may be incorporated in any martial art practice and hopefully provide insights into the time-honored Shaolin tradition.